Analysis of potential and direct sales strategies in the textile sector in the digital era - Wiryanto, Ricky; Husein, Alice Erni; Ng, Hana (Junal Ilmu Manajemen, 2024)
In today's digital era, technology has drastically changed the way we interact, shop and conduct business. One increasingly popular phenomenon is live selling, where sellers showcase and sell their products directly via digital platforms with real-time interaction with buyers. This study aims to analyze the potential and direct sales strategies for textile products in the context of digital markets. Using qualitative research methods, data was collected through interviews with industry players, online observations, and relevant literature studies.